Il caso dei Raeliani contro la Svizzera - Fattori, Gabriele (Studi Urbinati, A - Scienze giuridiche, politiche ed economiche, 2013)
7th March, 2001: the Swiss Raëlian Movement, a non-profit association which has been duly registered since 1977, asks the Neuchatel police for authorization to carry out a billposting campaign. The Raëlian poster itself presents nothing that is illegal, offensive or shocking. Authorisation, however, is denied. The local authorities fear that, if displayed in a public place, the poster could lead public opinion to believe that the town approves of the ideas of the Raëlian Movement. The problem is that the Association shows itself to be in favour of cloning, eugenics, geniocracy and a vaguely-defined practice of “sensual meditation” which foresees, or does not exclude, the participation of adolescents. 10th April, 2006: having exhausted the national instruments of jurisdictional defence, the Swiss Raëlian Movement raises the case before the European Court of Human Rights. 13th January, 2011: the First Section of the ECHR rejects the Association’s appeal. 20th June, 2011: the case is adjourned before the Grand Chamber of the ECHR. The case of the Swiss Raëlian Movement against Switzerland again presents the European Court of Human Rights with the problem of the balance of religious liberty and of freedom of expression in the present framework of social, cultural, religious and confessional pluralism. The case will predictably attract political attention and scientific debate. Finding itself under the scrutiny of the Grand Chamber, it does, in fact, seem destined to be of great relevance in the law of the European Court. Whilst awaiting the Grand Chamber’s definitive verdict on the case, the First Section of the ECHR has established that the legislative measure with which the national Swiss authorities denied the Raëlian Movement the authorization for the billposting campaign does not constitute a violation of art. 10 ECHR, if the measure was adopted on the basis of a national regulation with the objective of safeguarding health and morals, and the aim of preventing the commission of crimes. However, two dissenting opinions denounce the contradiction. The Swiss Raëlian Movement and its ideas are considered lawful. The same ideas, transmitted via a billposting campaign in a public place, seem to become unlawful. How is this possible?